Millimeter wave spectroscopy of the ground, first and second excited torsional states of acetone - Armieieva, I.A.; Ilyushin, V.V.; Alekseev, E.A.; Dorovskaya, O.A.; Margulès, L.; Motiyenko, R.A. (Радиофизика и радиоастрономия, 2016)
Purpose: spectrum investigation of the lowest three torsional states of acetone ( CH₃COCH₃ ) within the frequency ranges 34–150 and 480–620 GHz. Предмет и цель работы: исследование спектра первых трех торсионных состояний ацетона (CH₃COCH₃ ) в диапазонах 34÷150 и 480 ÷ 620 ГГц. Предмет і мета роботи: дослідження спектра перших трьох торсійних станів ацетону (CH₃COCH₃ ) у діапазонах 34 - 150 та 480 - 620 ГГц.